Innovative applications and developments of micro-pattern gaseous detectors - Francke, Tom; Peskov, Vladimir (Advances in chemical and material engineering (ACME) book series, 2014)
"This book focuses on the analysis and use of various gas detection systems, providing a detailed description of some of the most commonly used gas detectors and the science behind them"